2017
DOI: 10.5858/arpa.2015-0444-rs
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Antiglobulin Test: Indications, Interpretation, and Pitfalls

Abstract: The direct antiglobulin test (DAT; sometimes referred to as the "Coombs" test) continues to be one of the most widely used assays in laboratory medicine. First described about 70 years ago, it is elegantly simple in design, yet it is widely complex in its applications and interpretations, and it is prone to false-positive and false-negative results. The overall objective of our review is to provide practicing pathologists with a guide to identify situations when the DAT is useful and to highlight disease-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 39 publications
1
76
1
4
Order By: Relevance
“…In our review, we identified 39 PADH case reports in which clinical and immune hematological characteristics of patients, including DAT, were described. Seventeen The test is performed using anti-human globulins that cause, in case of a positive result, a visible agglutination reaction [12]. Different reagents can be used to elicit RBC agglutination: a polyspecific one recognizing both IgG and C3d and two monospecific agents recognizing only one of the two molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our review, we identified 39 PADH case reports in which clinical and immune hematological characteristics of patients, including DAT, were described. Seventeen The test is performed using anti-human globulins that cause, in case of a positive result, a visible agglutination reaction [12]. Different reagents can be used to elicit RBC agglutination: a polyspecific one recognizing both IgG and C3d and two monospecific agents recognizing only one of the two molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid antimalarial action of these drugs is related to "pitting" [7][8][9], a process whereby artemisinin-exposed parasites are removed from their host erythrocytes, within the spleen microcirculation. After being "pitted", once-infected erythrocytes re-enter the systemic circulation but with a reduced lifespan [8,10,11,12]. Thus, although "pitting" initially spares parasite-hosting erythrocytes, this positive effect may not be sustained [10].…”
Section: Introductionmentioning
confidence: 99%
“…B, New methylene blue stained supravital preparation shows red cells with Heinz bodies (yellow arrows) and rare red cells with golf-ball-like inclusions (red arrow) along with reticulocytosis remind hematopathologists that correlation of HPLCs with the clinical background, erythrocyte indices, and low-cost investigations such as HbH preparation and heat/isopropanolol instability tests may be of high yield in such cases 2. The inappropriate immunosuppressive therapy due to the single 2+ DCT in a recently transfused patient who may have developed clinically insignificant alloantibodies also highlights the importance of evaluating weak or low-grade positive DCT results from the perspective of the complete clinical scenario 10. Unlike unstable -globin chain variants, unstable -chain variants tend to be symptomatic only in homozygous or compound heterozygous states 1,[6][7][8][9].…”
mentioning
confidence: 99%
“…However, 5-10% of patients with AIHA are DAT negative [3]. The principal reasons for DAT-negative AIHA are: (a) RBCbound IgG being below the threshold of detection by standard methods; (b) low affinity of IgG; and (c) RBCbound IgA or rarely IgM [4]. To achieve greater sensitivity, alternative DAT methods have been developed, such as the micro-column (gel), solid-phase, polybrene, and flow cytometry methods, as well as enzyme-linked antiglobulin, immunoradiometric, and mitogen-stimulated tests [4].…”
mentioning
confidence: 99%
“…The principal reasons for DAT-negative AIHA are: (a) RBCbound IgG being below the threshold of detection by standard methods; (b) low affinity of IgG; and (c) RBCbound IgA or rarely IgM [4]. To achieve greater sensitivity, alternative DAT methods have been developed, such as the micro-column (gel), solid-phase, polybrene, and flow cytometry methods, as well as enzyme-linked antiglobulin, immunoradiometric, and mitogen-stimulated tests [4]. Moreover, because washing RBCs with room temperature saline causes the low-affinity antibodies to be eluted from RBCs, washing RBCs with cold saline or with low ionic strength saline (LISS) may be effective in detecting low-affinity antibodies.…”
mentioning
confidence: 99%